Bone marrow stromal cell-derived exosome combinate with fibrin on tantalum coating titanium implant accelerates osseointegration - Cui, Jian-Tong; Wang, Xin-Yuan; Mu, Xiao-Dan; Huang, Meng; Wang, Ya-Di; Luo, Qiang; He, Hui-Xia (Frontiers in Bioengineering and Biotechnology, 2023)
This study aims to present a sustainably releasing system of exosomes-fibrin combinate loaded on tantalum-coating titanium implants. We hope to investigate potential effects of the system on osseointegration between tantalum coating titanium implants and its surrounding bone tissue. Exosomes derived from rabbit bone marrow stromal cells (rBMSCs) and fibrin were deposited onto the micro-nanostructure tantalum coating surface (Ta+exo+FI) and compared to control groups, including tantalum coating (Ta), tantalum coating loaded exosomes (Ta+exo) and tantalum coating loaded fibrin (Ta+FI). The optimal concentration of loading exosomes, exosomes uptake capacity by BMSCs, and the effect of controlled-release by fibrin were assessed by laser scanning confocal microscope (LCSM) and microplate reader. The optimal concentration of exosomes was 1μg/μL. Adhesion, proliferation, and osteogenic differentiation ability of BMSCs on different materials were assessed in vitro. Finally, osseointegrative capacity of Ta, Ta+exo, Ta+FI, Ta+exo+FI implants in rabbit tibia were respectively evaluated with histology and bone-implant contact ratio (BIC%). It was demonstrated that exosome sustained-release system with fibrin loading on the tantalum coating was successfully established. Fibrin contribute to exosomes release extension from 2d to 6d. Furthermore, Ta+exo+FI significantly promoted adhesion, proliferation, and osteogenic differentiation of BMSCs. In vivo, the implants in Ta+exo+FI group displayed the highest osseointegrative capability than those in other groups. It is concluded that this exosome delivery system on the implants may be an effective way for tantalum coating titanium implants to promote osseointegration between implant and its surrounding bone tissue.